GIS of the chora of Cyrene: fortifications and Christian buildings in Late Antiquity. (7th November 2016) - Abdalrahim Sheriff Saad, A.; Farag Abdel Hati, S.; Antonelli, Sonia; Menozzi, Oliva; Petraccia, Veronica; Somma, Maria Carla
Abstract: The project of mapping the chora of Cyrene, for the team of Chieti University, started between 1999 and 2001 as a layer of a 'macro-GIS' of the area to the east of Cyrene, that is, the transect between Cyrene and El-Gubba/Qubbah. Because of the large scale of the area and the monumentality of the sites, the team is composed of several research units based around a large number of scholars and technicians. The project employs a suite of traditional methodologies for the study of landscape archaeology (surveys, GIS mapping, differential GPS, excavations), in combination with technologies integrating the knowledge of the territory (remote sensing on HD satellite photos, geomorphological reconstruction, laser scanning, archaeometric analysis, non-invasive geophysical prospection and infrared diagnostic analysis). The large quantity of data coming from this wide approach has been organised into a flexible and multilayer GIS. A joint team of Libyan and Italian archaeologists and technicians is testing a common protocol for monitoring the monuments and sites in the territory, using surveys and remote sensing analysis, which has intensified during these problematic periods, and regularly analysing satellite sets over the past four years. The project aims to map and document as much as possible in this territory, to identify the location of the region's so-called 'minor sites', which are numerous and almost unknown. They were, from the Late Classical to the Islamic periods, vital sites for the management of the local economy. This paper presents the main issues relating to settlements and sites in Late Antiquity, concentrating mainly on fortifications along the limes and basilicas within the area of the transect. Moreover, in the presentation of the data, the GIS approach has been integrated here with data coming both from the remote sensing and from more traditional research approaches, such as planimetrical and typological analysis of the buildings, study of the sources and detailed mapping of the building techniques. Abstract : إن مشروع رسم خرائط المنطقة المحيطة بالقيروان بالنسبة لفريق جامعة كياتي، كان قد بدأ بين عامي 1999 و 2001 كمرحلة من مراحل نظام المعلومات الجغرافية الشامل للمنطقة التي تقع شرق القيروان، بمعنى المقطع العرضي بين القيروان والقبة. يتكون الفريق من العديد من وحدات البحث المتمركزة حول عدد كبير من العلماء والفنيين، وذلك يعود للمساحة الكبيرة للمنطقة ولكبر المواقع الأثرية. يستخدم هذا المشروع تركيبة من المنهجيات لدراسة آثار الموقع (مسوحات، رسم خرائط عن طريق نظام المعلومات الجغرافية، نظام تحديد المواقع التفاضلي، التنقيب عن الآثار)، بالإضافة إلى التقنيات التي تجمع بين معرفة الإقليم (الاستشعار عن بعد باستخدام صور الأقمار الصناعية، إعادة التشكيل الجيوموفولوجي، المسح باستخدام الليزر، تحليل الآثار باستخدام الأساليب العلمية، الاستكشاف الجيوفيزيائي غير المجتاح والتحليل التشخيصي بالأشعة تحت الحمراء). إن الكمية الكبيرة من البيانات التي تم الحصول عليها من هذا الأسلوب الموسع قد تم تنظيمها ضمن نظام معلومات جغرافية مرن ومتعدد الطبقات . يقوم فريق ليبي وإيطالي مشترك من علماء الآثار والفنيين بتجربة مراسم مشتركة لمراقبة ومتابعة المباني والمواقع الأثرية في المنطقة باستخدام مجموعة من المسوحات وتحليل الاستشعار عن بعد، وهذا قد ازداد وتكثف خلال هذه الفترات الصعبة، والتحليل المنتظم للعديد من مجموعات صور الأقمار الصناعية خلال السنوات الأربعة الماضية. إن الهدف من المشروع في هذه المنطقة هو أن يتم رسم الخرائط وأن يتم التوثيق قدر الإمكان وذلك من أجل معرفة مواقع ما يسمى "بالمواقع الثانوية" في المنطقة، وهي عديدة وغير معروفة تقريباً. إن هذه المواقع من الفترة الكلاسيكية المتأخرة حتى الفترات الإسلامية مهمة جداً لإدارة الاقتصاد المحلي . تقدم هذه الورقة المواضيع الأساسية التي تتعلق بالاستيطان والمواقع في أواخر العصور القديمة، وتركز بشكل رئيسي على التحصينات الحدودية والكتدرائيات الرومانية في منطقة هذا المقطع العرضي . بالإضافة إلى ذلك، عند تقديم البيانات، فإن أسلوب استخدام نظام المعلومات الجغرافية قد تم جمعه هنا مع البيانات التي أتت من الاستشعار عن بعد ومع أساليب البحث التقليدية مثل التحليل البلانمتري والطبوغرافي للمباني ودراسة المصادر ورسم الخرائط التفصيلي لأساليب البناء.